Temporal trends in weight-based disparities in physical fitness of children: 30-years of continuous surveillance through Slovenian national system - Antonio Martinko; Rok Blagus; Gregor Jurak; Gregor Starc; Maroje Sorić (BMC, 2024)
Abstract Background Obesity in childhood has deleterious consequences for health while improving physical fitness can significantly reduce health risks related to high body mass index. We aimed to examine the evolution of disparities in physical fitness based on weight status among 7-15-year-olds in Slovenia between 1989 and 2019 and compare these trends across sex, age and socioeconomic status. Methods We used annual data collected within the SLOfit monitoring system in the period between 1989 and 2019, totalling 4,256,930 participants (about 137 000 per year). We examined cardiorespiratory fitness (600-m run test), muscular fitness (60-s sit-ups, bent arm hang, and standing broad jump test) and skill-related fitness (backwards obstacle course, 60-m dash, arm plate tapping). We grouped children according to the IOTF cut-offs for BMI to those living with normal weight or excess weight and estimated changes in physical fitness over time by fitting quantile regression models separately by sex and age group, and then using segmented regression to identify the patterns of trends over time. Results Weight-based disparities in physical fitness were large in 1989 and have further increased by 2019. The increase in disparities was generally around 5 percentiles larger in boys, and 10-15-year-olds compared to younger children. It was particularly pronounced for body core strength and speed in boys (up to 15 and 19 percentiles, respectively) and upper body strength and speed among girls (up to 13 percentiles). Most of the increase in disparities in health-related fitness accumulated during the 2010s, when the fitness of children generally improved, but much less so in children living with excess weight. Conclusions Despite recent improvements in population fitness levels, children with excess weight seem to be left behind, which adds to existing health inequalities. Our results should encourage policymakers to redesign policies aimed at promoting physical activity and enhancing physical fitness to make them more equitable and ultimately lead to reducing inequalities in fitness.